-3x+17-5x=12-(6x+3)

Simple and best practice solution for -3x+17-5x=12-(6x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+17-5x=12-(6x+3) equation:


Simplifying
-3x + 17 + -5x = 12 + -1(6x + 3)

Reorder the terms:
17 + -3x + -5x = 12 + -1(6x + 3)

Combine like terms: -3x + -5x = -8x
17 + -8x = 12 + -1(6x + 3)

Reorder the terms:
17 + -8x = 12 + -1(3 + 6x)
17 + -8x = 12 + (3 * -1 + 6x * -1)
17 + -8x = 12 + (-3 + -6x)

Combine like terms: 12 + -3 = 9
17 + -8x = 9 + -6x

Solving
17 + -8x = 9 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
17 + -8x + 6x = 9 + -6x + 6x

Combine like terms: -8x + 6x = -2x
17 + -2x = 9 + -6x + 6x

Combine like terms: -6x + 6x = 0
17 + -2x = 9 + 0
17 + -2x = 9

Add '-17' to each side of the equation.
17 + -17 + -2x = 9 + -17

Combine like terms: 17 + -17 = 0
0 + -2x = 9 + -17
-2x = 9 + -17

Combine like terms: 9 + -17 = -8
-2x = -8

Divide each side by '-2'.
x = 4

Simplifying
x = 4

See similar equations:

| f(-49)=-5x+1 | | 3/4=7/x-9 | | 5x-2y+3x+y= | | -21=-9+4x | | 2x+10=5x+10-3x | | f(-2)=x^2-5 | | 8-2+a-9a= | | F(-2)=5x^2-7x+10 | | (4x+6)=(3x+9) | | (6-15)*(4+5)= | | 10x-2(x+4)=4x-7 | | 40+50m=365 | | x+x+89=180 | | 5+11p=71 | | 128=2(6y-2) | | -4x+5x=-16 | | 15+x=3*x-15 | | 12+2x=24-2x | | (45-x)/x=23 | | 47=3+11h | | b(x^2)-ab=0 | | 7x-30=205 | | 7=w-(-7)5 | | x-10=6x+4 | | 6*x+4=x-11 | | x-26=10 | | 2x-2=-4(x-4) | | 10-3*x=x+4 | | -9=6+5v | | 3y+7=5y+1 | | 32x+(-32x+25)=12 | | 142,000,000/1.19 |

Equations solver categories